2013
DOI: 10.1111/cen.12178
|View full text |Cite
|
Sign up to set email alerts
|

A UK epidemic of testosterone prescribing, 2001–2010

Abstract: Many men in the UK might be receiving testosterone replacement therapy with neither clearly established indications nor robustly diagnosed hypogonadism. A national registry for men treated with testosterone and further evidence to improve current guidance (national and/or international) on the indications for testosterone replacement would be beneficial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(68 citation statements)
references
References 35 publications
2
65
0
1
Order By: Relevance
“…More recently, longitudinal studies have also confirmed that these findings have fuelled a substantial worldwide increase in testosterone prescription (10,11,12,13). Testosterone decline may not be an inevitable part of ageing, being related to adverse health and lifestyle factors, such as obesity; it may, therefore, be potentially preventable and reversible (5,6,7,14).…”
Section: Introductionmentioning
confidence: 93%
“…More recently, longitudinal studies have also confirmed that these findings have fuelled a substantial worldwide increase in testosterone prescription (10,11,12,13). Testosterone decline may not be an inevitable part of ageing, being related to adverse health and lifestyle factors, such as obesity; it may, therefore, be potentially preventable and reversible (5,6,7,14).…”
Section: Introductionmentioning
confidence: 93%
“…For men over the age of 50 years, a higher BMI was associated with a lower total testosterone level (Spearman's rho -0.24, p<0.001). 18 This study has demonstrated that of those men screened for hypogonadism, 21.2% were potentially hypogonadal. Thus, over a 10-year period, screening in primary care identified a significant minority of men who had potential hypogonadism, regardless of whether the local Cheshire accredited laboratory cut-off was used or the BSSM criteria were applied.…”
Section: Body Mass Index (Bmi)mentioning
confidence: 85%
“…Until then mostly intramuscular testosterone enanthate or cypionate had been . Currently mostly transdermal gels and intramuscular testosterone undecanoate tend to be used [7,8] and these preparations, if properly administered, result in physiologic serum testosterone levels.…”
Section: Testosterone Preparations and Modes Of Applicationmentioning
confidence: 99%
“…Some recent publications indicate that testosterone is frequently prescribed without proper patient follow-up [7,8,87,88]. However, although careful monitoring at regular intervals is emphasized in most of the current guidelines [6], they are not consistent concerning follow-up intervals and the parameters to be evaluated.…”
Section: Monitoring Of Testosterone Substitutionmentioning
confidence: 99%
See 1 more Smart Citation